If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x + 12z = 30 Solving 20x + 12z = 30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12z' to each side of the equation. 20x + 12z + -12z = 30 + -12z Combine like terms: 12z + -12z = 0 20x + 0 = 30 + -12z 20x = 30 + -12z Divide each side by '20'. x = 1.5 + -0.6z Simplifying x = 1.5 + -0.6z
| 8x-13=6x-3 | | -x-3=-4x-9 | | x(-2)=(-18) | | x-8=-2x+22 | | 5(a+4)-3.2=14.3 | | x-16=-x-30 | | 5x-4=-2x-25 | | -3x-17=-44 | | 8x-7=3x-17 | | x+(.4x*.5x*.145x)=19130 | | Y=-0.8t+40 | | 8x+14=4x+34 | | 113-303= | | 33(-5)= | | 6=-10d+2 | | 33x-5= | | 2x^2-4x+103=0 | | 2x^2-4x-103=0 | | 6-7d=-3D+2 | | 15-2x=0 | | -6x^2-2x-1=0 | | 8=-5x-3 | | -366+k=170 | | 17+4(3+q)-a= | | 3x-5(0.6x-1)=3 | | 4(3+9)+10a-41= | | M+-2=67 | | 6x-24=4x-2-6 | | 2(3-3x)=94 | | 6x+8+2x=4(5+x) | | 3f+47-2f=40 | | 2-(2x-1)+7x=10 |